Penerapan Teknik Komplementer Pengunaan Gymball untuk Mempercepat Penurunan Kepala - Nurhasanah Nurhasanah; Septi Tri Aksari; Dahlia Arief Rantauni; Norif Didik Nurimanah; Ellyzabeth sukmawati (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Background: Changes due to pregnancy are experienced by all women, starting from the digestive system, cardiovascular and musculoskeletal systems. Gradual bodily changes from a pregnant woman's increased weight cause the woman's posture and gait to change. Increased abdominal distension which makes the pelvis tilt forward, decreased abdominal muscle tone and the center of gravity shifts forward so that there is a tendency for the waist muscles to shorten if the abdominal muscles are stretched, causing an imbalance in the pelvic muscles which can cause discomfort in the lower back and also have an impact on lowering the baby's head. Objective: This study was to determine the relationship between using a gymball and lowering the fetal head in third trimester pregnant women.Method: This research uses primary and secondary data with a case study approach, namely providing complementary care in the form of using a gym ball to help lower the fetal head.Results: Pregnant women in the third trimester experienced head loss when using a gym ball.Conclusion: Based on the results of data analysis, using a gymball can help the decline process.Suggestion: It is hoped that PMB in Pesanggrahan village will become a forum and facilitator for pregnant women and women giving birth whose first stage is abnormal by using a gym ball to help lower the head and speed up the labor process.